The Long-Term Presence of SARS-CoV-2 on Cold-Chain Food Packaging Surfaces Indicates a New COVID-19 Winter Outbreak: A Mini Review - Chi, Yuhua; Wang, Qingxiu; Chen, Guosheng; Zheng, Shiliang (Frontiers in Public Health, 2021)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is a highly infectious virus that is transmitted primarily through droplets or by coming in close contact with an infected person. In 2020, there was a global outbreak of COVID-19, resulting in an unprecedented global burden of disease, health care costs, and had a significant economic impact. Recently, SARS-CoV-2 was detected on the outer packaging of imported cold chain items in China and has led to virus transmission events, causing great concern. This paper analyses the factors of SARS-CoV-2 survival and transmission in different places and environments, especially the characteristics of low temperatures and object surfaces. It was found that SARS-CoV-2 could survive on surfaces of cold and moist objects in the cold chain for more than 3 weeks, potentially causing COVID-19 transmission. We believe that the low-temperature environment in winter may accelerate the spread of the outbreak and new outbreaks may occur. Overall, SARS-CoV-2 transmission that is susceptible to low winter temperatures is critical for predicting winter pandemics, allowing for the appropriate action to be taken in advance.